ASSOCIATION OF GENETIC DIVERGENCE WITH HETEROSIS, COMBINING ABILITY AND MEAN VALUE FOR QUANTITATIVE TRAITS IN POPCORN (ZEA MAYS VAR. EVERTA) - N. V. SONI,; S. M. KHANORKAR, (The Bioscan, 2013)
The study was aimed to analyze the genetic diversity among popcorn inbred lines using Random Amplified Polymorphic DNA profiling and to associate it with heterosis, specific combining ability and mean values of hybrids for quantitative traits viz., days to 50% tasseling, days to 50% silking, days to maturity, plant height, ear height, seed index, grain yield per plant, dry fodder yield per plant and popping expansion obtained in diallel study. The highest heterosis was observed for grain yield (99.16%) followed by dry fodder yield (96.57%). Fifteen polymorphic RAPD primers were used for polymerase chain reaction amplification. In dendrogram, most of the genotypes were clustered in a single cluster except I-07-35-7-3 which grouped in another cluster. The estimate of genetic diversity varies from 0.49 to 0.86. Correlation coefficients (r) ranged from -0.472 to 0.295. These correlations were extremely low or non-significant for all the quantitative traits. The results depicted that RAPD technique was efficient in detecting polymorphism in popcorn populations. Genetic diversity showed no significant association with all parameters of hybrid performance for days to maturity, plant height and seed index.